Characterization Of Spatial Variability Of Soil Nutrients At USM Engineering Campus - Baharudin, Fauzi (Universiti Sains Malaysia, 2005)
The general objective of this study is to examine the spatial variability of soil nutrients and pH in a flat region under subtropical climate using statistical and geostatistical methods. The soil samples were taken from 50 points in the Universiti Sains Malaysia, Engineering Campus, Nibong Tebal, Penang, Malaysia. Collection of the soil data were conducted by systematic sampling and the Global Positioning System (GPS) was used to determine the sample site locations. Semivariogram analysis was performed for the spatial soil nutrients to examine the autocorrelation among the data set using GS+ software. The results showed that the soil nutrients potassium (K), phosphorus (P) and nitrate have moderate spatial dependence, while there was a strong spatial dependence for pH with available lag distance of 0.18 km to 0.41 km. The SURFER software used to produce kriged maps for the spatial distribution and the results indicated the existing of significant spatial variability of the soil nutrients in the study area.